1981
DOI: 10.1056/nejm198109033051001
|View full text |Cite
|
Sign up to set email alerts
|

Assay of an Activity in the Serum of Patients with Disorders of Thrombopoiesis That Stimulates Formation of Megakaryocytic Colonies

Abstract: We have recently described an in vitro clonal assay system for human megakaryocyte-progenitor cells or megakaryocytic colony-forming units (CFU-M). Serum specimens from patients with quantitative platelet disorders were screened for the capacity to alter in vitro megakaryocyte-colony formation. Serum from 11 patients with hypomegakaryocytic thrombocytopenia significantly enhanced the formation of CFU-M-derived colonies (200 to 1840 per cent). Neither serum from eight patients with thrombocytopenia and normal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1

Year Published

1982
1982
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 22 publications
5
39
1
Order By: Relevance
“…[21][22][23][24] On the other hand, it was described that TPO levels were high when thrombocytopenia was due to megakaryocyte deficiency, and low when due to increased platelet destruction, 19 and that serum megakaryocyte colony-stimulating activity levels appeared to be inversely related to marrow megakaryocyte numbers. 25 In the present study, we could clearly demonstrate using a sensitive ELISA that human TPO levels also changed inversely with the number of platelets after myelosuppressive chemotherapy. Furthermore, when platelets were transfused into patients at the time of nadir of platelet counts, elevated TPO levels dropped rapidly by around 4.0 fmol/ml within 1 h of the platelet transfusion, while platelet counts increased by around 28 × 10 9 /l.…”
Section: Discussionsupporting
confidence: 58%
“…[21][22][23][24] On the other hand, it was described that TPO levels were high when thrombocytopenia was due to megakaryocyte deficiency, and low when due to increased platelet destruction, 19 and that serum megakaryocyte colony-stimulating activity levels appeared to be inversely related to marrow megakaryocyte numbers. 25 In the present study, we could clearly demonstrate using a sensitive ELISA that human TPO levels also changed inversely with the number of platelets after myelosuppressive chemotherapy. Furthermore, when platelets were transfused into patients at the time of nadir of platelet counts, elevated TPO levels dropped rapidly by around 4.0 fmol/ml within 1 h of the platelet transfusion, while platelet counts increased by around 28 × 10 9 /l.…”
Section: Discussionsupporting
confidence: 58%
“…16,17 Attempts to use megakaryocyte colony formation to study thrombopoiesis in ITP have given contradictory results. Some groups, culturing ITP bone marrow, have found increased numbers of megakaryocyte colony-forming units (CFU-Ms), 18,19 whereas others have found decreased numbers of CFU-Ms. 20 Similarly, one group 21 reported that ITP plasma did not affect CFU-M formation by normal cells, yet another group 18 noted increased CFU-M formation in the presence of ITP serum.…”
Section: Discussionmentioning
confidence: 99%
“…Urine (5,6), serum (7), and plasma (8,9) obtained from patients with hypomegakaryocytic thrombocytopenia have been shown to promote the formation of megakaryocyte colonies by marrow mononuclear cells in vitro. Phytohemagglutininstimulated leukobyte-conditioned media as well as normal bone and lung conditioned media contain a similar activity (10).…”
Section: Introductionmentioning
confidence: 99%